2019
DOI: 10.1155/2019/7172930
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Guided Capsule Endoscopy in Pediatric Patients with Abdominal Pain

Abstract: Background and Aims. Magnetically guided capsule endoscopy (MGCE) offers a noninvasive method of evaluating both the gastric cavity and small intestine; however, few studies have evaluated MGCE in pediatric patients. We investigated the diagnostic efficacy of MGCE in pediatric patients with abdominal pain. Patients and Methods. We enrolled 48 patients with abdominal pain aged 6–18 years. All patients underwent MGCE to evaluate the gastric cavity and small intestine. Results. The cleanliness of the gastric card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Furthermore, MGCE as a non-invasive procedure is well tolerated by pediatric patients. After scanning the stomach, MGCE still has enough battery power to record clear images of the entire small bowel ( Xie et al, 2019 ; Qian et al, 2018 ; Lai et al, 2020 ). MRE is preferred for pediatric CD patients because no ionizing radiation is involved, with high soft tissue contrast and a low incidence of adverse events (( Rimola et al, 2011 ; Hokama et al, 2020 ; Minordi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MGCE as a non-invasive procedure is well tolerated by pediatric patients. After scanning the stomach, MGCE still has enough battery power to record clear images of the entire small bowel ( Xie et al, 2019 ; Qian et al, 2018 ; Lai et al, 2020 ). MRE is preferred for pediatric CD patients because no ionizing radiation is involved, with high soft tissue contrast and a low incidence of adverse events (( Rimola et al, 2011 ; Hokama et al, 2020 ; Minordi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results show that MCCG is feasible and safe in children over 6 years old, and more studies are needed to further study the efficacy of MCCG in children [42]. Xie et al [43] performed MCCG examinations on 48 patients with abdominal pain aged 6-18 years to evaluate the diagnostic effects. The results showed that the visualization rates of the cardia, fundus, body, angle, antrum, and pyloric mucosa were 84.8%, 83.8%, 88.5%, 87.7%, 95.2%, and 99.6%, respectively.…”
Section: Robotic-type Mccementioning
confidence: 99%
“…33 Furthermore, pediatric patients, who are unable to tolerate EGD, can safely undergo successful gastric examination with the robotic MCE system. 34 Owing to its high diagnostic performance and safety, the robotic MCE system for human gastric examinations is currently approved by the Chinese FDA. 35 Recently, a second-generation MCE has been developed, which has greater image resolution, shortened examination duration, and improved maneuverability compared to the first-generation MCE.…”
Section: Ankon Technology Co Ltdmentioning
confidence: 99%
“…Because the MCE system shows a good diagnostic detection rate for gastric lesions, it can be a good alternative for EGD in high-risk patients [ 33 ]. Furthermore, pediatric patients, who are unable to tolerate EGD, can safely undergo successful gastric examination with the robotic MCE system [ 34 ]. Owing to its high diagnostic performance and safety, the robotic MCE system for human gastric examinations is currently approved by the Chinese FDA [ 35 ].…”
Section: Active Locomotion Under Magnetic Controlmentioning
confidence: 99%